Yeast biomass, an optimised product with myriad applications in the food industry. Issue 2 (December 2015) - Pérez-Torrado, Roberto; Gamero, Esther; Gómez-Pastor, Rocío; Garre, Elena; Aranda, Agustín; Matallana, Emilia
Abstract: Background: Yeasts, especially Saccharomyces cerevisiae and related species, have been used by humans since ancient times. In past centuries, the increased demand in yeast-related products has converted yeast biomass into a valuable product, and has forced the generation and optimisation of industrial yeast biomass production processes, which currently generate vast quantities of yeasts yearly. Scope and approach: In this article, we review key aspects for the yield first produced empirically, but by also using recent yeast physiology knowledge. We summarise the classical and latest yeasts biomass applications in the food industry, which range from the yeast extract used as an additive in many commercially prepared foods, to the nutritional yeast supplement used to complement diets. Finally, we present advanced molecular studies that have revealed the strong impact of the cellular stress suffered during the industrial production process on yeast biomass yield and fermentative efficiency. Key findings and conclusions: The large number of applications enhances the importance and demand of this industrial product and the relevance of its production in a sustainable way. The new findings at molecular level will permit new designs and strategies to enhance quality and quantity of commercial products. Highlights: In the last years, yeast biomass has been widely used in the food industry. Yeast biomass production process is optimized to obtain high yields. Molecular studies revealed stressful situations in this process. Optimal oxidative stress response is important to increase biomass yield.